2015
DOI: 10.1159/000434691
|View full text |Cite
|
Sign up to set email alerts
|

Serum Vitamin D Status as a Predictor of Prognosis in Patients with Acute Ischemic Stroke

Abstract: Background: Low 25-hydroxyvitamin D (25(OH)D) concentrations have been shown to predict risk of cardiovascular disease and all-cause mortality. Although the prevalence of 25(OH)D deficiency is high in patients with acute stroke, the prognostic value of 25(OH)D in stroke has not been clearly established. The purpose of this study was to determine whether the baseline serum 25(OH)D level was associated with the functional outcome in patients with acute ischemic stroke. Methods: From June 2011 to January 2014, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
65
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(72 citation statements)
references
References 34 publications
7
65
0
Order By: Relevance
“…There is some evidence that vitamin D deficiency is associated with an increased risk for vascular diseases and it also increases general mortality [19, 51]. In the study by Park and coworkers [19] only minority (13.6%) of patients had optimal vitamin D levels of ≥75 nmol/l at the time of stroke.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is some evidence that vitamin D deficiency is associated with an increased risk for vascular diseases and it also increases general mortality [19, 51]. In the study by Park and coworkers [19] only minority (13.6%) of patients had optimal vitamin D levels of ≥75 nmol/l at the time of stroke.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Park and coworkers [19] only minority (13.6%) of patients had optimal vitamin D levels of ≥75 nmol/l at the time of stroke. A recent French study [52] also showed that vitamin D deficiency is very frequent in IS patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually, vitamin D deficiency in stroke patients preceded stroke, and the prevalence of vitamin D deficiency is more evident in stroke patients than general medical patients. On the other hand, vitamin D supplementation in post-stroke patients may play a role in the prevention of recurrent stroke and improves the functional outcome after stroke [147,148,149,150]. …”
Section: Vitamin D Deficiencies and Ischemic Strokementioning
confidence: 99%
“…It has also been shown that 25(OH)D levels are lower in patients with stroke [12, 13]. Moreover, 25(OH)D deficiency increases risk of stroke and even affects stroke prognosis [14], causing more stroke-related fatal outcomes [15]. In contrast, the number of studies examining the association between increased PTH levels and cardiovascular diseases [6, 16], mortality [11, 17], and particularly, stroke [18, 19] is quite limited.…”
Section: Discussionmentioning
confidence: 99%